Colonic Dieulafoy's Lesion: A Rare Cause of Lower Gastrointestinal Hemorrhage and Review of Endoscopic Management. (19th October 2014) - Ma, Christopher; Hundal, Rajveer; Cheng, Edwin J.
Abstract : Dieulafoy's lesions are a rare cause of gastrointestinal hemorrhage. Extragastric Dieulafoy's lesions are even more uncommon. We report the case of a 75-year-old woman who presented with gastrointestinal bleeding from a transverse colonic Dieulafoy's lesion. She presented with two episodes of melena followed by one episode of fresh blood per rectum. In addition, there was associated presyncope and anemia (hemoglobin 69 g/L) in the setting of supratherapeutic warfarin anticoagulation (INR 6.2) for nonvalvular atrial fibrillation. Esophagogastroduodenoscopy was negative for an upper GI source of bleeding but on colonoscopy an actively oozing Dieulafoy's lesion was identified in the transverse colon. Bipolar cautery and hemostatic endoclips were applied to achieve hemostasis. Clinicians should consider this rare entity as a potential cause of potentially life-threatening lower gastrointestinal bleeding and we review the endoscopic modalities effective for managing colonic Dieulafoy's lesions.